A hundred years in the elucidation of the structures of natural products. (1st March 2017) - Hanson, James
The development in the strategies for elucidating the structures of natural products from 1916 to 2016 are reviewed revealing the transition from chemical to spectroscopic methods and using examples drawn from the chemistry of terpenoids and steroids.